Serum and cellular ribavirin pharmacokinetic and concentration–effect analysis in HCV patients receiving sofosbuvir plus ribavirin. (13th May 2015) - Rower, Joseph E.; Meissner, Eric G.; Jimmerson, Leah C.; Osinusi, Anu; Sims, Zayani; Petersen, Tess; Bushman, Lane R.; Wolfe, Pamela; McHutchison, John G.; Kottilil, Shyamasundaran; Kiser, Jennifer J.
Abstract: Objectives: Ribavirin concentrations may impact hepatitis C virus (HCV) treatment outcome. We modelled ribavirin serum and intracellular ribavirin monophosphate (RBV-MP) and ribavirin triphosphate (RBV-TP) pharmacokinetics in red blood cells (RBC) using samples collected during the NIAID SPARE trial to explore associations with treatment outcome and the development of anaemia. Patients and methods: Individuals infected with HCV genotype 1 (GT1) received 400 mg of sofosbuvir and either low-dose or weight-based ribavirin as part of the NIAID SPARE trial. Concentrations were modelled using NONMEM and associated with treatment outcomes using unpaired t -tests or Pearson's rho correlations. Results: Average day 14 RBV-MP concentrations were higher in subjects with haemoglobin nadir <10 g/dL relative to patients with haemoglobin nadir ≥10 g/dL (6.54 versus 4.48 pmol/10 6 cells; P = 0.02). Additionally, day 14 RBV-MP average concentrations trended towards being higher in subjects that achieved sustained virological response (SVR) as compared with patients who relapsed (4.97 versus 4.09 pmol/10 6 cells; P = 0.07). Receiver operating characteristic curves suggested day 14 RBV-MP concentration thresholds of 4.4 pmol/10 6 cells for SVR ( P = 0.06) and 6.1 pmol/10 6 cells for haemoglobin nadir <10 versus ≥10 g/dL ( P = 0.02), with sensitivity and specificity ≥60%. Dosing simulations showed that 800 mg of ribavirin once daily produced day 14 RBV-MP concentrations within the 4.4–6.1 pmol/10 6 cells range. Conclusions: RBV-MP concentrations in RBC at day 14 were related to anaemia and SVR. A therapeutic range was identified for RBV-MP in persons with HCV GT1 disease receiving 24 weeks of sofosbuvir plus ribavirin, suggesting a potential pharmacological basis for individualized ribavirin dosing in IFN-free regimens.